The Role of the Kuntau Sinar Pahlawan Community in Preserving Traditional Martial Arts - Azizah, Nur; Syaharuddin, Syaharuddin; Subroto, Wisnu (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research examines the role of the Kuntau Sinar Pahlawan Community in preserving the traditional martial art of Kuntau as part of the cultural heritage of Tanah Laut Regency, South Kalimantan. Kuntau not only represents physical skills but also contains philosophical, spiritual, and social values that form the cultural identity of the Banjar people. The method used was descriptive qualitative through observation, interviews, and literature study. The results showed that this community actively preserves Kuntau through regular training, cultural performances, and adaptation to technological developments through digital media. In addition, the preservation strategies implemented include documentation of the movement, development of an internal curriculum, and integration of local values in every learning process. The community has managed to maintain Kuntau's existence through adaptive strategies, despite facing challenges such as a lack of interest from the younger generation, limited resources, and a lack of support from the government and financial support. The conclusion of the research confirms that the preservation of traditional martial arts requires synergy between the community, government, and society in order to maintain cultural sustainability.